The future of births via medically assisted reproduction in Italy:Scenarios to 2050 - Alessandra Burgio; Cinzia Castagnaro; Gustavo De Santis; Daniele Vignoli; Agnese Vitali (PLoS ONE, 2026)
Delayed childbearing is increasingly common in high-income societies, contributing to rising demand for medically assisted reproduction (MAR). This paper presents nine possible scenarios of the future share of MAR births on the total number of births in Italy, a country internationally known for its latest-late mean age at childbearing. We combined the latest (2023) official data and three hypotheses on the evolution of maternal mean age at childbirth (no change, slow ageing, rapid ageing) with three hypotheses on the age-specific MAR-related fertility rates (no change, moderate increase, rapid increase). Our projections indicate that changes in the age structure of women of reproductive age will likely have a negligible effect on future MAR prevalence. In contrast, delayed childbearing and continued expansion of MAR use could raise the share of MAR births from 4.3% in 2023 to 11–12% by mid-century, with a plausible upper bound exceeding 15% under sustained trends. These results underscore the growing demographic, social and economic significance of MAR in Italy and highlight important implications for public health planning, resource allocation, and policies aimed at supporting earlier childbearing.